Identification of a 43-kDa protein in human liver cytosol that binds to the 3'-untranslated region of CYP2A6 mRNA - GILMORE, James; ROTONDO, Francesca; PELLETIER, Anne-Marie; LAMARRE, Jonathan; ALAOUI-JAMALI, Moulay; KIRBY, Gordon M (Biochemical pharmacology, 2001)
Hepatic expression of cytochrome P450 2A6 (CYP2A6) varies widely in humans and is induced during hepatitis; however, the mechanism regulating CYP2A6 has not been established. The murine orthologue Cyp2a5 is regulated post-transcriptionally by mRNA stabilization. A 43-kDa protein that binds to the 3'-untranslated region (3'-UTR) of Cyp2a5 mRNA has been identified, but its role in mRNA stabilization is unclear. We hypothesized that similar interactions occur between cytosolic proteins in human liver and CYP2A6 3'-UTR mRNA. We identified, by RNA electrophoretic mobility shift assay, an hepatic cytosolic protein that binds specifically to sequences in the 3'-UTR of CYP2A6. Complexes did not form with denatured proteins and were eliminated with proteinase K digestion. Complex formation was inhibited with a molar excess of unlabeled CYP2A6 RNA but not by non-specific competitor RNA. Protein-mRNA interactions were not affected by probe denaturation, suggesting that RNA secondary structure is not essential for binding. UV cross-linking of complexes revealed RNA-binding proteins in both human and mouse liver cytosols with molecular masses of approximately 43 kDa. Using truncated RNA probes corresponding to various lengths of CYP2A6 mRNA, the protein-binding site was localized to a 50-nucleotide region between bases 1478 and 1527 of the 3'-UTR. Complex formation with hepatic cytosolic protein from four human subjects correlated with levels of hepatic CYP2A6 microsomal protein, suggesting a possible regulatory role. Further characterization of the RNA-binding protein, the primary binding site, and the influence of this interaction on CYP2A6 mRNA stability will help to elucidate the relevance of these findings to the post-transcriptional control of CYP2A6.